Safe faecal sludge emptying and transport: compliance challenges and models for a public good - Grisaffi, Claire; Leinster, Paul; Mugo, Kariuki; Drabble, Sam; Parker, Alison (IWA Publishing, 2025)
In the 81 countries where most urban dwellers rely on faecal sludge (FS) emptying and transport, services are frequently provided by a heterogeneous private sector. Considering the responses of service providers is essential to ensuring that the regulatory frameworks put into place achieve their intended outcomes and safeguard public and environmental health. Combining a literature review and expert practitioner input, we identify priority challenges for scaling safe FS emptying and transport (E&T) services and use these to adapt a holistic model of business compliance. We confirm well-documented challenges such as cost structures for compliance with regulation, the perception of services as low status, and an inadequate enabling environment. We identify the importance of trust in building voluntary compliance as a novel issue for sanitation but widely discussed in the regulation literature. We also identify a distinct role for the regulator as a catalyst for change. The role of disgust as a policy barrier and the application of behavioural theory to building compliance are areas warranting further research. This is the first paper to explicitly consider the regulation of FS E&T through a compliance lens, linking established areas of the regulation literature to new findings in urban sanitation.
Keywords: 41 Environmental Sciences; 4104 Environmental Management; 8.1 Organisation and delivery of services; 8.3 Policy, ethics, and research governance; Generic health relevance; 11 Sustainable Cities and Communities; 4104 Environmental management; regulation; sanitation; urban